Data-source interoperability service for heterogeneous information integration in ubiquitous enterprises. Issue 3 (August 2015) - Pang, L.Y.; Zhong, Ray Y.; Fang, J.; Huang, George Q.
Abstract In a ubiquitous environment, various enterprise information systems (EISs) are used for supporting daily operations. Besides, with the support with Auto-ID technology, enterprises are able to collect real-time operation data but these data are continuously pushed to different EISs. Data without processing are meaningless and not able to support managerial decision-makings. The wide use of EISs and Auto-ID devices within an enterprise increases the difficulties in data interoperability among difficult data sources. Since data sources from applications and devices are characterized by multiple types of heterogeneities, such as communication protocols, blinding methods, and developing environments, the difficulty in managing heterogeneous data sources is highly raised. Information integration in ubiquitous enterprises is critical because it has a significant influence on the efficiency and effectiveness of decisions. This article presents an innovative Data-Source Interoperability Service (DSIS) that serves as a middleware for providing a querying and information integration service for heterogeneous data sources. The DSIS applies software agent technology that is capable of accomplishing tasks in an autonomous way without human intervention. Operations provided by DSIS Agent are converted into standard web services. The agent-based services are managed by DSIS Universal Description, Discovery and Integration registry (DSIS-UDDI) which facilitates collaboration among agents. Additionally, the DSIS platform also provides set of visual tools for users to manage and (re)configure different data sources within enterprises.